Tinjauan Hukum Islam Terhadap Pengolahan Lahan Pertanian - Majduddin, Muhammad (CENDEKIA, 2022)
This article aims to describe a review of Islamic law on agricultural land processing. The method used in this study is a normative and empirical method with the type of research field research by collecting data used observations, interviews, and documentation to obtain valid information about the situation that occurs in the field. The results of the study are 1. The practice of agricultural land processing with a profit-sharing system in Tanjung Putih Hamlet, Prancak Village, Sepulu District, Bangkalan Regency in practice the land owner enters into an agreement to share agricultural land with the cultivator by mutual trust between the two parties and mutually provides benefits and profits, with seeds, fertilizers issued from the cultivator. Then in the agreement, the land owner and the cultivator do not determine the period of time for the implementation of land cultivation and the wages given from each harvest with the distribution of the proceeds 1 to 2, namely one for the landowner and two for the cultivator. Because the landowner here only provides land and only receives the results of each harvest. 2. The practice of profit sharing on agricultural land in Tanjung Putih Hamlet, Prancak Village, Sepulu District, Bangkalan Regency, if reviewed from Madhab Hanafi, the contract carried out in Tanjung Putih Hamlet is not valid, and if reviewed according to Madhab Hambali, the implementation of land cultivation carried out in Tanjung Putih Hamlet is legal.